PREDIKSI JUMLAH FATALITAS DENGAN METODE ARTIFICIAL NEURAL NETWORK BERDASARKAN UNDANG-UNDANG LALULINTAS TAHUN 2009 DAN KARAKTERISTIK WILAYAH - Supratman Agus (Jurnal Transportasi, 2015)
Abstract Law No. 22 of 2009, on Road Traffic and Road Transport, stated that the fatality data should be complemented with data coming from the hospital. The fatality data reported by the police is the data from the place of traffic accident. Two variables, population and number of vehicles, have been used to predict the number of traffic accident fatalities in many countries. The purpose of this study was to develop a multivariable Artificial Neural Network model for the prediction of fatality in Indonesia. The predictive model was built with input population data of 2007-2010 from the 26 counties and cities in West Java. The study results showed that the ANN three variables with two hidden layer (ANN3-2HL) model is the best-fatality prediction models and prediction of the number of fatalities in West Java Province for 2010 is 3,872 people, which means greater than the number in the data of the Indonesian National Police. Model ANN3-2HL is expected to be used to predict the actual number of fatalities in road safety studies in Indonesia. Key words: traffic, road safety, accidents, fatalities  Abstrak Undang-Undang Nomor 22 Tahun 2009, tentang Lalulintas dan Angkutan Jalan, menyatakan bahwa data fatalitas perlu dilengkapi dengan data yang berasal dari rumah sakit. Data fatalitas yang dilaporkan oleh Kepolisian berasal dari lokasi kejadian. Untuk memprediksi jumlah fatalitas kecelakaan lalulintas di banyak negara, digunakan dua variabel, yaitu jumlah penduduk dan jumlah kendaraan. Tujuan studi ini adalah mengembangkan model Artificial Neural Network multivariabel untuk prediksi fatalitas di Indonesia. Model prediksi dibangun dengan input data populasi tahun 2007-2010 dari 26 kabupaten-kota di Jawa Barat. Hasil studi menunjukkan bahwa model ANN tiga variabel dengan dua hidden layer (ANN3-2HL) merupakan model prediksi fatalitas terbaik dan jumlah prediksi fatalitas tahun 2010 di Provinsi Jawa Barat adalah 3.872 orang, yang berarti lebih banyak dari data Kepolisian Republik Indonesia. Model ANN3-2HL diharapkan dapat digunakan untuk meramalkan jumlah fatalitas aktual pada studi keselamatan jalan di Indonesia. Kata-kata kunci: lalulintas, keselamatan jalan, kecelakaan, fatalitas